Cytotoxic and Pro-Apoptotic Effects of a Sub-Toxic Concentration of Fluvastatin on OVCAR3 Ovarian Cancer Cells After its Optimized Formulation to Melittin Nano-Conjugates - Badr-Eldin, Shaimaa M.; Alhakamy, Nabil A.; Fahmy, Usama A.; Ahmed, Osama A. A.; Asfour, Hani Z.; Althagafi, Abdulhamid A.; Aldawsari, Hibah M.; Rizg, Waleed Y.; Mahdi, Wael A.; Alghaith, Adel F.; Alshehri, Sultan; Caraci, Filippo; et al. (Frontiers in Pharmacology, 2021)
Fluvastatin (FLV) is a hydroxymethylglutaryl coenzyme A (HMG‐CoA) reductase inhibitor often used to lower total and low-density lipoprotein (LDL) cholesterol and for the prevention of adverse cardiovascular events. This drug as well as melittin (MEL), the major component of honeybee venom (Apis mellifera), have shown antineoplastic activity, then representing promising approaches for cancer therapy. However, adverse effects related to the use of FLV and MEL have been reported and very few studies have been carried out to obtain an optimized formulation allowing to combine the two drugs and then maximize the anti-cancer activity, then minimizing the needed dosage. In the present study, an optimized formulation in terms of minimized particle size and maximized zeta potential was investigated for its cytotoxic potential in human OVCAR3 ovarian cancer cells. FLV-MEL nano-conjugates, containing a sub-toxic concentration of drug, demonstrated an improved cytotoxic potential (IC50 = 2.5 µM), about 18-fold lower, compared to the free drug (IC50 = 45.7 µM). Cell cycle analysis studies demonstrated the significant inhibition of the OVCAR3 cells proliferation exerted by FLV-MEL nano-conjugates compared to all the other treatments, with a higher percentage of cells accumulating on G2/M and pre-G1 phases, paralleled by lower percentage of cells in G0/G1 and S phases. The synergistic antineoplastic activity of FLV and MEL combined in the optimized formula was also showed by the marked pro-necrotic and pro-apoptotic activities, the latter mediated by the modulation of BAX/BCL-2 ratio in favor of BAX. Our optimized FLV-MEL formulation might therefore represent a novel path for the development of a specific and more effective antineoplastic drugs directed against ovarian cancer.